2005
DOI: 10.24200/jams.vol10iss1pp5-12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alternate Bearing on Leaf and Fruit Mineral Composition at Different Developmental Stages of Date Palm Fruits

Abstract: ‫اﻟﺒﺤﺚ.‬ ‫ھﺬا‬ ‫ﻣﺜﻞ‬ ‫أﺳﺘﻤﺮارﻳﺔ‬ ‫اﻟﻰ‬ ‫اﻟﺤﺎﺟﺔ‬ ‫ﻋﻠﻰ‬ ‫اﻟﻨﺘﺎﺋﺞ‬ABSTRACT: Samples of leaflets and fruits at different stages were collected from 6 "on-palms" and 6 "off-palms" (15-16 years) of the Fard Cultivar. Samples were dried, ashed and digested. Macro and micronutrient concentrations of K, Ca, Mg, Na, Fe, Zn, Cu and Mg were determined by ICP-AES and N was measured by Kjeldhal method. Significant changes in the elemental concentrations of leaf and fruit occurred between Kimri (green color) and Bisir (yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…It is probable that an "on" palm could be determined as having a B Table 1. Summarising mean elemental concentrations (in mg/kg) in "on" and "off" fruit and leaflets for each development stage for most of the elements considered in this review [2] concentration in the leaflets of greater than 3.5 mg/kg during Bisir, whereas an "off" palm has less than this ( Table 1). This demonstrates that a lack of B could contribute to the poor growth seen in "off" palms [30].…”
Section: Boron (B)mentioning
confidence: 99%
See 4 more Smart Citations
“…It is probable that an "on" palm could be determined as having a B Table 1. Summarising mean elemental concentrations (in mg/kg) in "on" and "off" fruit and leaflets for each development stage for most of the elements considered in this review [2] concentration in the leaflets of greater than 3.5 mg/kg during Bisir, whereas an "off" palm has less than this ( Table 1). This demonstrates that a lack of B could contribute to the poor growth seen in "off" palms [30].…”
Section: Boron (B)mentioning
confidence: 99%
“…Calcium is an essential element and helps maintain ionic balance in plants [27]. For the date palm, it has been found that significant differences in the Ca concentration exist between the "on" and "off" trees during one of the fruit developmental stages [2]. More specifically, the "off" palm leaflets had higher Ca levels than the "on" palm leaves during the Rutab stage [2] ( Table 1).…”
Section: Calcium (Ca)mentioning
confidence: 99%
See 3 more Smart Citations